Electrocatalytic/photocatalytic properties and aqueous media applications of 2D transition metal carbides (MXenes). Issue 5 (October 2019) - Sinopoli, Alessandro; Othman, Zakarya; Rasool, Kashif; Mahmoud, Khaled A.
Graphical abstract: Characteristic electrocatalytic and photocatalytic properties of MXenes and their aqueous media applications. Abstract: The 2D transition metal carbides (MXenes) are increasingly considered among of the most promising 2D nanomaterials, because of their unique properties such as hydrophilic nature, metallic conductivity, large surface-area-to-volume ratio, and active surface functionalities. This has led to their growing utilization in water/wastewater treatment and environmental remediation applications, including water purification membranes, heavy metal removal, capacitive deionization, and bactericidal agents. This account will focus on the key characteristic properties of MXenes such as high metallic/electronic conductivity, and catalytic activity, and their utilization for the electrocatalytic and photocatalytic-based environmental remediation applications. We will also address the key challenges facing MXene-based materials in aqueous media and possible mitigation routs.